16S rRNA gene sequencing and MALDI TOF mass spectroscopy identification of Leuconostoc mesenteroides isolated from Algerian raw camel milk - Hanane Fatma Chentouf; Fouzia Rahli; Zineb Benmechernene; Jorge Barros-Velazquez (Journal of Genetic Engineering and Biotechnology, 2023)
Abstract Background Eighty-three strains of Leuconostoc mesenteroides were isolated from Algerian raw camel milk. Based on morphological, biochemical, and physiological characters tests, strains were identified as Ln. mesenteroides subsp. mesenteroides. Seven strains had a remarkable antagonistic and probiotic characterization. The present study aims at identifying these strains by means of 16 s rRNA gene sequencing and Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS), extending phenotypic and genotypic studies done previously. Results The phyloproteomic dendrograms of the studied strains based on MALDI-TOF MS provided the same identification with more intraspecific information from the 16S rRNA gene sequencing based on phylogenetic analysis. The latter were in agreement with the previous biochemical/physiological identification, the seven isolated strains were Ln. mesenteroides subsp. mesenteroides. Conclusions Remarkably, MALDI-TOF MS fingerprinting was found to be effective enough as 16S rRNA gene sequencing identification, allowing faster and more reliable analysis than biochemical/physiological methods.